Upaya Meningkatkan Efektivitas Manajemen Kesehatan Keluarga Dengan TBC Melalui Dukungan Keluarga Dalam Kepatuhan Minum Obat - Dwi Yuningsih; Assa Nur Fadhilah; Anis Prabowo; Sri Handayani; Agus Hidayat (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
Background: Tuberculosis (TB) is a disease caused by the bacterium Mycobacterium tuberculosis. These bacteria are able to live for months in a cool and dark place, especially in a humid place. TB germs can cause infection in the lungs so it is called pulmonary TB. In addition to infecting the lungs, TB germs can enter the blood vessels and spread throughout the body. Research Objectives: To explore the available research evidence on Improving the Effectiveness of Family Health Management with TB through Family Support in Drug Adherence. Research Methodology: This study uses a descriptive exploratory design of research articles to explore the best available evidence in the last three years. The research instrument uses an online website media to search for research articles with the Open Journal System (OJS), namely publications in national (preferred) and international journals that are indexed and can be accessed openly, which is limited to the period of publication in the last one to three years until get 9 articles for literature review. Research Results: This study produced 9 articles that supported the title of the researcher and then reviewed and analyzed to prove related to efforts to improve the effectiveness of family health management with tuberculosis through family support through medication adherence. Conclusion: family support can increase the effectiveness of family health management with tuberculosis through medication adherence.Stroke is a disease that causes major disability, a stroke patient who experiences paralysis will experience impaired mobilization so that the bone area will stand out as a result of experiencing ischemia and hypoxia tissueresulting in pressure sores.